Beyond silks and spices, east and west - Rosaye, Jean-Paul (2016)
The main idea I would like to develop and assess in this paper was upheld and defended by Paul Ricoeur in his famous dictum that ‘To say self is not to say I’, and its corollary that ‘the shortest route from self to self is through the other’. That there is an implicit dialectic is underlined in another short passage taken from Ricoeur’s book Oneself as Another: